2021
DOI: 10.3389/fped.2021.646830
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of 3D Digital Models Using GOSLON Yardstick Index: Exploring Confounding Factors Responsible for Unfavourable Treatment Outcome in Multi-Population Children With UCLP

Abstract: To evaluate dental arch relationship (DAR) using GOSLON Yardstick and also to explore the association between multiple factors (age, gender, UCLP types, UCLP side, Family history of cleft, family history of Class III malocclusion, techniques of cheiloplasty, techniques of palatoplasty) and DAR in children unilateral cleft lip and palate (UCLP) in different populations. Two hundred fifty-five laser scanned 3D digital models (LS3DM) of UCLP children (5–12 years) from Malaysia, Bangladesh, and Pakistan were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…The majority of available studies referred to Asian populations and reported conflicting results. Yew et al [ 17 ] did not find any association between sex and the DAR outcome in Malay UCLP subjects, while Haque et al [ 32 ] reported more favourable DARs among Bangladeshi females with UCLP. Considering the multitude of elements influencing the treatment of UCLP, it is difficult to explain the reasons for such findings.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of available studies referred to Asian populations and reported conflicting results. Yew et al [ 17 ] did not find any association between sex and the DAR outcome in Malay UCLP subjects, while Haque et al [ 32 ] reported more favourable DARs among Bangladeshi females with UCLP. Considering the multitude of elements influencing the treatment of UCLP, it is difficult to explain the reasons for such findings.…”
Section: Discussionmentioning
confidence: 99%